Creative Economy Development through Digital Marketing for MSMEs Actors in Sembung Village, Bojonegoro - Muttaqin, Muh. Syaukin; Hana, Ubaid Aisyul; Nurlailah, Nurlailah; Susilowati, Susilowati (Sahwahita: Community Engagement Journal, 2025)
Digital transformation has become an urgent need for Micro, Small, and Medium Enterprises (MSMEs) in facing increasingly competitive economic competition. In Sembung Village, the majority of MSMEs still market their products conventionally, without utilizing digital media and without adequate product legality. This community service activity aims to: (1) introduce the concept and practice of social media-based digital marketing; (2) assist in the process of creating attractive and informative product label designs; and (3) encourage the processing of food legality through PIRT permits for local MSMEs. The method used is Participatory Action Research (PAR), which actively involves MSMEs in all stages of the activity. Data collection was carried out through interviews, observations, and documentation, with triangulation techniques to validate the findings. The results of the activity showed that digital marketing training was able to improve MSMEs' understanding of social media-based promotional strategies. As many as 75% of participants began to actively use platforms such as Instagram and WhatsApp Business to reach a wider market. In addition, several MSMEs succeeded in having new product label designs and had completed the PIRT permit application process. These findings indicate that digital intervention and product legality contribute positively to strengthening the competitiveness of village MSMEs. This activity recommends further assistance to ensure the sustainability of optimal digital marketing implementation.